Villa del Santissimo a waterfront destination retail/entertainment district - Garrido, Emilio M.; Silvestre, Danilo A.; Santaromana, Francis L. (Quezon City College of Architecture, University of the Philippines Diliman, 1999)
The conceptual framework plan made by the Asian Institute of Technology Alumni of Cebu (AITAC) contain, among others, a set of key investment programs and projects for the historic downtown waterfront district. This coherent framework is aimed at realizing the Cebu City Waterfront Development Project (CCWDP), an urban renewal program initiated by the City Government of Cebu spearheaded by the Honorable Mayor Alvin Garcia.
With reference to the said framework plan, this thesis entitled Villa del Santissino - a waterfront destination retail/entertainment district, proposes a development in a form of mixed-use project at the waterfront area with the end in view of revitalizing the blighted and declining historic downtown district. The proposed project of the thesis is consistent with the said urban renewal program of the City Government of Cebu.
While mixed-use development is not a panacea for the much touted "urban crisis" it can accomplish multiple public objectives: making significant contribution to city revenues, making the most of existing infrastructure and public building program, saving public sector costs, treating blight and decay, integrating public uses.
Which makes mixed-use development one of my ideal choice of project for the most ambitious feats of gentrification/urban renewal program in Cebu City: to create on this notorious historic downtown/waterfront district cleaner and more friendly environment.
On the other hand, the creations of new urban form by rehabilitation programs pose a threat to existing historical monuments and sites, valuable cultural heritage, at present unevenly maintained and preserved. That makes the integration of concepts of historic conservation necessary in the development of this thesis. Maintaining and protecting the historical context of the place is one of the main objective of the thesis. Furthermore, as a waterfront development, the essence of the design intervention for the rehabilitation of this historic downtown waterfront is drawn from principles and theories of urban design. These are in view of creating a rich imagery of this historic district in a way that would generate appreciation and enjoyment of the place.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Waterfronts